Floquet-Engineered System-Reservoir Interaction in the Transverse Field Ising Model - Valderrama-Quinteros, N (John Wiley and Sons Inc, 2025)
Periodically driving a quantum many-body system can drastically change its properties, leading to exotic non-equilibrium states of matter without a static analog. In this scenario, parametric resonances and the complexity of an interacting many-body system are pivotal in establishing non-equilibrium states. A Floquet-engineered transverse field Ising model for the controlled propagation in one dimension of spin waves is reported. The underlying mechanisms behind the proposal rely on high-frequency drivings using characteristic parametric resonances of the spin lattice. Many-body resonances modulating spin-spin exchange or individual spin gaps inhibit interactions between spins thus proving a mechanism for controlling spin-wave propagation and a quantum switch. The schemes may be implemented in circuit QED with direct applications in coupling–decoupling schemes for system-reservoir interaction and routing in quantum networks. © 2025 Wiley-VCH GmbH.